PERANCANGAN ILUSTRASI DAN LAYOUT BUKU ENSIKLOPEDIA JET TEMPUR TERBAIK DUNIA - FERALDI BRIMA, Drs. Syafwan, M.Si., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
Encyclopedia is one kind of book. In there studying about one topic or category information. By Encyclopedia people can learn and increase their experience on one of topic knowledge. Designing illustration and Layout of encyclopedia best jet fighter in the world make people easy to understand the visual and information in there.Designing illustration and Layout best jet fighter in the world encyclopdedia purpose to information can be deservet to people in printed media. Designing illustration and Layout in printed media like book expect can be contribut on education section. Designing illustraton and layout may help people understand carefully what information they wants and interested to follow.